The victims of unethical human experiments and coerced research under National Socialism - Weindling, Paul; von Villiez, Anna; Loewenau, Aleksandra; Farron, Nichola (Endeavour (New series), 2016)
•Human experiments were more extensive than often assumed with a minimum of 15,750 documented victims.•Experiments rapidly increased from 1942, reaching a high point in 1943 and sustained until the end of the war.•There were more victims who survived than were killed as part of or as a result of the experiments. Many survived with severe injuries.•Victims came from diverse nationalities with Poles (Jews and Roman Catholics) as the largest national cohort.•Body parts, especially from euthanasia killings, were often retained for research and teaching after 1945. There has been no full evaluation of the numbers of victims of Nazi research, who the victims were, and of the frequency and types of experiments and research. This paper gives the first results of a comprehensive evidence-based evaluation of the different categories of victims. Human experiments were more extensive than often assumed with a minimum of 15,754 documented victims. Experiments rapidly increased from 1942, reaching a high point in 1943. The experiments remained at a high level of intensity despite imminent German defeat in 1945. There were more victims who survived than were killed as part of or as a result of the experiments, and the survivors often had severe injuries.